Effect of freeze/thaw on aggregation and transport of nano-TiO2 in saturated porous media. Issue 6 (5th May 2020) - Farner, Jeffrey M.; De Tommaso, Jacopo; Mantel, Heather; Cheong, Rachel S.; Tufenkji, Nathalie
Abstract : Research has focused on nanoparticle (NP) aggregation and transport behavior in saturated granular porous media, but few studies have looked at the effect that temperature variability associated with winter conditions will have on engineered NPs. Abstract : Extensive research has been conducted on nanoparticle (NP) aggregation and transport behavior in saturated granular porous media, but few studies to date have looked at the effect that temperature variability associated with winter conditions will have on engineered NPs. To investigate the effect of these fluctuations above and below freezing on particle stability, titanium dioxide (TiO2 ) NPs were subjected to a freeze/thaw (FT) cycle, which led to aggregation and increased deposition in a saturated granular porous medium. We compare NP aggregation and transport behavior for two commercially available formulations of TiO2, which exhibited differences in aggregation in suspension and deposition to a quartz sand. A single FT cycle induced TiO2 aggregation, increased the heterogeneity of aggregate sizes, and increased deposition in a saturated porous media. Nanoparticles subjected to FT in the presence of organic matter underwent greater aggregation and deposition relative to NPs held at 10 °C. Calculations of attachment efficiency for a given amount of deposition are shown to depend on aggregate size, highlighting a limitation in assigning a single value for the attachment efficiency in polydisperse samples. This study suggests that NP behavior and transport in cold weather climates will differ from warmer environments and that the increased cycling of freezing and thawing associated with climate change will further influence the fate of NPs.